2010
DOI: 10.3390/ijerph7041597
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Distribution of Microfungi in a Treated Municipal Water Supply System in Sub-Tropical Australia

Abstract: Drinking water quality is usually determined by its pathogenic bacterial content. However, the potential of water-borne spores as a source of nosocomial fungal infection is increasingly being recognised. This study into the incidence of microfungal contaminants in a typical Australian municipal water supply was carried out over an 18 month period. Microfungal abundance was estimated by the membrane filtration method with filters incubated on malt extract agar at 25 °C for seven days. Colony forming units were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 23 publications
2
25
0
2
Order By: Relevance
“…(5.79%-9.42%). Their occurrences in drinking water or biofilms have been reported (Doggett, 2000;Sammon et al, 2010). Recently, using atomic force microscope, Abe et al (2011) found that biofilm aggregates were embedded in an extensive network of filamentous fungi during the development of drinking-water biofilm, and indicated that the fungal structure may assist in reinforcing biofilm adhesion to a substratum surface.…”
Section: Eukaryotic Communitiesmentioning
confidence: 99%
“…(5.79%-9.42%). Their occurrences in drinking water or biofilms have been reported (Doggett, 2000;Sammon et al, 2010). Recently, using atomic force microscope, Abe et al (2011) found that biofilm aggregates were embedded in an extensive network of filamentous fungi during the development of drinking-water biofilm, and indicated that the fungal structure may assist in reinforcing biofilm adhesion to a substratum surface.…”
Section: Eukaryotic Communitiesmentioning
confidence: 99%
“…Aspergillus species are saprophytic moulds widely distributed in soil, decaying vegetation, dust, bioaerosols and different aquatic environments, in which they are expected to contribute to the degradation of pollutants (Sammon et al 2010;Pereira et al 2013;Pearson et al 2015;Ma et al 2015;Oliveira et al 2015). Aspergillus fumigatus, which is responsible for severe pathologies in humans and birds (Van Waeyenberghe et al 2013), has been isolated from hospital water systems and plumbing drains (Hayette et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Wash water from apple packing and processing houses can contain as much as 10 4 conidia mL -1 of P. expansum and often inadvertently end up in the ground near such facilities. The presence of fungi in drinking water is widespread (Sammon et al 2010;Pereira et al 2009;Hageskal et al 2006). Penicillium species appear to be frequent inhabitants of tap water based on surveys carried out in several countries (reviewed by Siqueira et al 2011); thus, they readily survive water treatment practices (Hageskal et al 2006).…”
Section: Introductionmentioning
confidence: 99%